Association between the neutrophil-to-lymphocyte ratio and the incidence of diabetic retinopathy: a systematic review and meta-analysis - Jin, Wenshu; Tu, Xiaofang; Chen, Xiaopei; Zhang, Jinghong (Frontiers in Endocrinology, 2026)
BackgroundAccumulating evidence has indicated a possible relation of the neutrophil-to-lymphocyte ratio (NLR) to diabetic retinopathy (DR) incidence. However, current findings remain inconclusive.MethodsPubMed, Embase, Web of Science, as well as Cochrane Library, were thoroughly retrieved before March 20, 2025, for eligible studies examining the relation of NLR to DR incidence. The primary outcomes included DR incidence assessed as a categorical and a continuous variable. Categorical data were expressed as odds ratios (ORs) with 95% confidence intervals (CIs), and continuous data were expressed as standardized mean differences (SMDs) with 95% CIs.Results35 studies comprising 49,664 patients were encompassed. Pooled results demonstrated a significant relation between elevated NLR level and a greater DR risk, when analyzed as a categorical variable (OR = 1.48, 95% CI: 1.34-1.64; p < 0.00001) and as a continuous variable (SMD = 0.47, 95% CI: 0.36-0.59; p < 0.00001). Sensitivity analyses demonstrated the robustness of our findings. Subgroup analyses showed that regional differences were the main source of heterogeneity.ConclusionsAn increased NLR may be significantly related to a greater risk of DR among individuals with diabetes. However, further prospective and multicenter investigations are necessary to corroborate these findings.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=1054742, identifier CRD420251054742.